2018
DOI: 10.2478/jee-2018-0082
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between grain size in self-developed soft magnetic composites and the Grucad hysteresis model

Abstract: Soft magnetic composites (SMCs) have been in the spotlight of magnetic community due to their unique properties which can easily be tailored up to a specific application. The present paper is focused on the possibility to develop SMC cores produced from iron powder mixed with suspense polyvinyl chloride. Important processing parameters like grain size are correlated with the parameters of a simple phenomenological hysteresis model developed by the Grucad research group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Forthcoming work is focussed on modelling more complex magnetization cycles like DC-biased loops (Jastrzębski et al , 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forthcoming work is focussed on modelling more complex magnetization cycles like DC-biased loops (Jastrzębski et al , 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we point our attention to the important practical problem for the designers of magnetic circuits: is it possible to find optimal processing parameters for SMC cores? A recently published companion study by Jastrzębski et al , 2018b) discusses the effect of grain size on magnetic properties in self-developed cores.…”
Section: The Grucad Modelmentioning
confidence: 99%
“…e choice of iron powder is the result of previous research on soft magnetic composites (SMCs). In the works [12][13][14][15], it was found that there is a relationship between the size of grains and the level of magnetic induction (generally, larger grains allow us to achieve a higher B at the same level of H). e weight proportions of the components have been selected so that the magnetic paint is suitable for offset printing.…”
Section: Methodsmentioning
confidence: 99%
“…In the low-dimensional GRUCAD model [8][9][10][11], considered by us for the description of hysteresis curves of soft magnetic composites (SMCs) [12,13], the irreversible and reversible magnetization effects are decoupled and described with separated sets of equations, which also reminds the extension of T (x) model described in this section.…”
Section: The Reversible Magnetization Processesmentioning
confidence: 99%